Parachordoma in gluteal region : A Case Report (TAJ: Journal of Teachers Association, 2009)
A 26 year old man with a painful left gluteal mass was found to have parachordoma. It had been noted 5 months prior to the time of the examination. Physical examination revealed diffuse swelling with elastic consistency and ill-defined margins. The tumor mass was measured as being 12 x 10 cm. An incisional biopsy was performed and diagnosed as parachordoma by histopathological examination.TAJ 2009; 22(1): 269-271